Ghana's Poverty Monitoring System - Canagarajah, Sudharshan (World Bank, Washington, DC, 2012)
The note features the particularly serious problem of poverty monitoring systems in Sub-Saharan Africa, namely through the case of Ghana, where in 1987, the first Living Standards Measurement Survey (LSMS) was conducted. It notes though, that over the years data collection in Ghana improved substantially, where recent LSMS data for the country, became the centerpiece of Consultative Group meetings, undoubtedly a "good practice" that deserves special mention. Lessons, and trends that facilitated the process address the increased upstream planning in data entry, data cleaning, and data analysis, in addition to capacity building, and training prior to launching surveys. Nonetheless, areas for further improvement still indicate prevailing institutional bottlenecks, and delays in the release of counterpart funds, which are conducive to weak procurement practices, aggravated by the continued, over-reliance on external consultants.